2014
DOI: 10.1016/j.appet.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Associations between child emotional eating and general parenting style, feeding practices, and parent psychopathology

Abstract: Emotional eating is the tendency to eat in response to negative emotions. Prior research has identified a relationship between parenting style and child emotional eating, but this has not been examined in clinical samples. Furthermore, the relationship between specific parenting practices (e.g., parent feeding practices) and child emotional eating has not yet been investigated. The current study examined relationships between child emotional eating and both general and specific parenting constructs as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(73 citation statements)
references
References 48 publications
2
67
0
4
Order By: Relevance
“…A recent study measuring parental feeding practices and children's eating behaviors in a longitudinal cohort of Norwegian families ( N = 797, ages 6 and 8 years) found instrumental feeding practices (i.e., using food as a reward) at age 6 predicted increased EOE at age 8 (Steinsbekk, Belsky, & Wichstrom, ). Similarly, further research has established that children whose parents actively control their emotions through feeding engage more in EOE (Braden et al., ; Tan & Holub, ). In addition, children whose parents highly control their food intake express more EOE behaviors (Farrow, Haycraft, & Blissett, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study measuring parental feeding practices and children's eating behaviors in a longitudinal cohort of Norwegian families ( N = 797, ages 6 and 8 years) found instrumental feeding practices (i.e., using food as a reward) at age 6 predicted increased EOE at age 8 (Steinsbekk, Belsky, & Wichstrom, ). Similarly, further research has established that children whose parents actively control their emotions through feeding engage more in EOE (Braden et al., ; Tan & Holub, ). In addition, children whose parents highly control their food intake express more EOE behaviors (Farrow, Haycraft, & Blissett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal research suggesting that childhood bullying and peer influence increase the risk of obesity in adulthood supports the increasing importance of peers in later childhood (Takizawa, Danese, Maughan, & Arseneault, ). Earlier in development, previous research has suggested that parents who use food to soothe elicit emotional eating behavior in their children (Braden et al., ). Further evidence for the importance of parental feeding comes from an experimental study ( n = 25 mother–child dyads) showing that children whose mothers use food to regulate emotions overconsume in the absence of hunger when induced with a negative mood (Blissett, Haycraft, & Farrow, ).…”
mentioning
confidence: 99%
“…This association may compromise the child’s ability to appropriately interpret hunger and satiety cues leading to increased energy intake and risk for childhood obesity. Or, it may result in the development of an emotional eating style which has been identified as an obesogenic trait linked to parent emotional feeding (e.g., food to soothe), poor diet, and weight gain (Braden et al, 2014; Braet & Van Strien, 1997; Sleddens, Kremers, De Vries, & Thijs, 2010). More research is needed to test the link between parent use of FTS, children’s emotional eating, and childhood obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Variously labelled emotional feeding (Wardle, Sanderson, Gutherie, Rapoport, & Plomin, 2002), feeding to soothe, (Stifter, Anzman - Frasca, Birch, & Voegtline, 2011), feeding to calm (Baughcum et al, 2001; Evans et al, 2011), or feeding to regulate emotions (Musher-Eizenman & Holub, 2007), this practice has been shown recently to have negative consequences with relation to children’s eating behavior and style. Studies have shown that parents who report using food to soothe (FTS) 1 have children who are more likely to develop emotional eating styles (Braden et al, 2014) and have poorer diets, e.g., lower fruit intake/energy dense snacking (Rodenburg, Kremers, Oenema, & van de Mheen, 2013; Sleddens et al, 2014). While the evidence is mounting that FTS contributes to child eating and diet, the few studies that have examined FTS and child weight have produced mixed findings.…”
Section: Introductionmentioning
confidence: 99%
“…Of importance to the present inquiry, children who are susceptible to the mood enhancing effect of food may elicit and reinforce emotional feeding in their parents—that is, parents who experience that their child is easily soothed by food may be more likely to emotionally feed their child (Rodgers et al., ). Over time, this is hypothesized to strengthen the connection between emotions and food for the child (Braden et al., ). This assumption has received some initial support with respect to early childhood; Rodgers et al.…”
Section: Emotional Feedingmentioning
confidence: 99%